2017
DOI: 10.1016/j.molmet.2017.04.011
|View full text |Cite
|
Sign up to set email alerts
|

The glucoregulatory actions of leptin

Abstract: BackgroundThe hormone leptin is an important regulator of metabolic homeostasis, able to inhibit food intake and increase energy expenditure. Leptin can also independently lower blood glucose levels, particularly in hyperglycemic models of leptin or insulin deficiency. Despite significant efforts and relevance to diabetes, the mechanisms by which leptin acts to regulate blood glucose levels are not fully understood.Scope of reviewHere we assess literature relevant to the glucose lowering effects of leptin. Lep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
119
0
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(129 citation statements)
references
References 238 publications
1
119
0
9
Order By: Relevance
“…matrix metallopeptidase 12, Mmp12; procollagen c-endopeptidase enhancer, Pcolce ) (19,20) and cytokines (e.g. coagulation factor VII, F7; leptin, Lep; secreted frizzled-related protein 1, Sfrp1 ) (2123). These genes are not differentially expressed in white adipose from the same animals, and they are not differentially expressed in low fat-fed brown or white adipose between 20 and 30 weeks ( Supplemental Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…matrix metallopeptidase 12, Mmp12; procollagen c-endopeptidase enhancer, Pcolce ) (19,20) and cytokines (e.g. coagulation factor VII, F7; leptin, Lep; secreted frizzled-related protein 1, Sfrp1 ) (2123). These genes are not differentially expressed in white adipose from the same animals, and they are not differentially expressed in low fat-fed brown or white adipose between 20 and 30 weeks ( Supplemental Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%
“…This cluster is mainly characterized by its response to leptin (LEP), which was also identified as one of the main functions of FB6. LEP is a proteohormone secreted by white adipocytes, targeting the hypothalamus and thereby regulating the energy balance of the body . Interestingly, our transcriptome analysis revealed that FB3 and FB6 highly and FB1 to a minor degree express the LEP‐receptor ( LEPR , Figure S15).…”
Section: Discussionmentioning
confidence: 97%
“…LEP is a proteohormone secreted by white adipocytes, targeting the hypothalamus and thereby regulating the energy balance of the body. 55,56 Interestingly, our transcriptome analysis revealed that FB3 and FB6 highly and FB1 to a minor degree express the LEP-receptor (LEPR, Figure S15). Since application of LEP on mouse wounds has been shown to promote wound healing, 57,58 and blocking of LEP delays wound healing, 57 our data suggest a contribution of FB3 and FB6 to wound healing in response to LEP.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, if the function of leptin is to stimulate lipolysis, why would leptin levels decrease in situations where lipolysis needs to be activated? One possibility is that the effects of leptin on lipolysis depend on insulin levels 96 and on the sympathetic tone.…”
Section: Leptin and Adipose Functionsmentioning
confidence: 99%